Peningkatan Keterampilan Penggunaan Software Quantum Gis (QGIS) pada Kelompok Guru Geografi Madrasah Aliyah (MA) Se Kabupaten Batang - Indrayati, Ariyani; Aji, Ananto; Narendra, Alfa; Setyaningsih, Wahyu; Aji, Halim Sukma (Universitas Sebelas Maret, 2025)
Improving the quality of teachers must and must always be improved in order to support learning activities in schools, especially geography teachers. In geography subjects, teachers must be able to teach students directly how to make thematic maps digitally, therefore, learning in class is not only limited to theory but also directly practiced so that students can understand more easily and learning in class becomes effective. However, the conditions in the field are that teachers still experience difficulties and obstacles in teaching students how to practice making maps digitally using software. One of the obstacles faced by teachers is because the price of the software is so expensive, therefore our community service team tries to use free software (open source), namely Quantum GIS (QGIS). The development of geographic information system technology, especially software, is developing very rapidly and quickly. therefore it is important for teachers to be able to follow technological developments in the field of geographic information systems, especially Quantum GIS (QGIS) software. This community service activity aims to improve practical skills and also update the development of geographic information system technology, especially using Quantum GIS (QGIS) software in the geography teacher group in the Madrasah Aliyah environment in Batang Regency. The activity will be carried out in the form of socialization to provide knowledge for geography teachers regarding updates on the development of geographic information system technology, as well as workshop activities and practical training in data processing and digital map making using Quantum GIS (QGIS) software..Peningkatan kualitas guru harus dan wajib selalu ditingkatkan dalam rangka mendukung kegiatan pembelajaran disekolah dalam hal ini khususnya guru geografi. Pada mata pelajaran geografi guru harus mampu mengajarkan kepada siswa secara langsung bagaimana cara membuat peta tematik secara digital oleh karena itu pembelajaran dikelas bukan hanya sebatas teori namun juga langsung dipraktikan sehingga siswa lebih mudah memahami dan pembelajaran dikelas menjadi efektif. Namun kondisi dilapangan faktanya para guru masih mengalami kesusahan dan kendala dalam mengajarkan kepada siswa bagaimana praktik membuat peta secara digital menggunakan software. Kendala yag dihadapi guru salah satunya adalah karena harga software yang begitu mahal, oleh karena itu kami tim pengabdi mencoba untuk menggunakan software yang tidak berbayar (opensource) yaitu Quantum GIS (QGIS) Perkembangangan teknologi sistem informasi geografis khususnya pada software sangat berkembang pesat dan cepat. oleh karena itu hal ini menjadi penting bagi guru untuk dapat mengikuti perkembangan teknologi dibidang sistem informasi geografis khususnya software Quantum GIS (QGIS) . Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan keterampilan praktek dan juga update perkembangan teknologi sistem informasi geografis khususnya menggunakan software Quantum GIS (QGIS) pada kelompok guru geografi di lingkungan Madrasah Aliyah di Kabupaten Batang. Kegiatan akan dilaksanakan dalam bentuk sosialisasi untuk memberikan pengetahuan bagi guru-guru geografi terkait update perkembangan teknologi sistem informasi geografis, serta kegiatan workshop dan pelatihan praktek pengolahan data dan pembuatan peta digital menggunakan software Quantum GIS (QGIS).